Parathyroid adenoma associated with neurofibromatosis type 1 - Aundrya Montgomery; Neetu Krishnan; Katerina Dukleska; Fabiola Balarezo; Christine Trapp; Nancy Dunbar; Christine Finck (Elsevier, 2021)
Parathyroid adenomas are a rare incidence in pediatric patients and typically occur secondary to primary hyperparathyroidism. Furthermore, the relation between neurofibromatosis 1 causing parathyroid adenoma is poorly understood. Here, we present the successful management of an 11-year old female adolescent diagnosed with primary hyperparathyroidism undergoing surgical excision of a parathyroid adenoma.